Electric field directed self-assembly of block copolymers for rapid formation of large-area complex nanopatterns. Issue 5 (28th September 2017) - Jeon, Hyun Uk; Jin, Hyeong Min; Kim, Ju Young; Cha, Seung Keun; Mun, Jeong Ho; Lee, Kyung Eun; Oh, Jung Jae; Yun, Taeyeong; Kim, Jun Soo; Kim, Sang Ouk
Abstract : We investigate the unusually rapid directed self-assembly of block copolymer (BCP) thin films by imposing an in-plane electric field. Abstract : We investigate the unusually rapid directed self-assembly of block copolymer (BCP) thin films by imposing an in-plane electric field. Blending short chain BCPs dramatically enhances the generically retarded chain diffusivity for BCP self-assembly in thin films. In addition, photopatterned, few-layer solution-cast chemically modified graphene is introduced as a disposable and versatile electrode for electric field applications. A variety of laterally ordered self-assembled lamellar BCP nanopatterns are attained within a 10 min time scale, including an arbitrary large-area unidirectionally oriented lamellar array.